Tele-ophthalmology versus Traditional Fundus Photography for Diabetic Retinopathy Screening: A Comparative Meta-analysis of Diagnostic Accuracy, Cost-Effectiveness, and Health Policy Uptake - Ramzi Amin; Dio Asgira Rizky (HM Publisher, 2024)
Diabetic retinopathy (DR) remains a leading cause of preventable blindness globally, imposing a significant public health burden. Effective screening is paramount for early detection and timely intervention. Traditional fundus photography (TFP), often requiring specialized equipment and personnel, faces access challenges. Tele-ophthalmology (TO) has emerged as a potential solution to improve screening coverage. However, rigorous comparative evidence regarding its diagnostic accuracy relative to established TFP methods, its economic viability, and factors influencing its adoption into health policy and routine practice remains fragmented. This systematic review and meta-analysis aimed to synthesize the evidence comparing TO and TFP for DR screening across these critical domains. We conducted a systematic literature search adhering to PRISMA guidelines across PubMed, EMBASE, and Web of Science databases for studies published between January 1st, 2013, and December 31st, 2023. Keywords included